Perturbation Theory for Abstract Volterra Equations. (21st March 2013) - Kostić, Marko
Abstract : We consider additive perturbation theorems for subgenerators of ( a, k )-regularized C -resolvent families. A major part of our research is devoted to the study of perturbation properties of abstract time-fractional equations, primarily from their importance in modeling of various physical phenomena. We illustrate the results with several examples.